al-Qaḍāyā al-Ijtimāʿiyyah fī Qiṣṣah Qaṣīrah “Ṭabaq al-Aṣl” li-ʿAlī al-Ṭanṭāwī (Dirāsat al-Wāqiʿiyyah al-Ishtirākiyyah) - Putri Mauna Al-ghina; Syarifuddin; Sumardi; Rasyad; Ivan Aulia Trisnady (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
The short story “Ṭabaqu al-Aṣl” by ʿAlī al-Ṭanṭāwī portrays a variety of social problems that reflect the conditions of Arab society at the time of its writing. This study aims to identify and analyze the social issues represented in the text. The research employs a qualitative descriptive method, drawing upon written data contained within the work. Data collection was carried out through close reading, note-taking, and library research. Analytical procedures include identification, interpretation, critical analysis, and the formulation of conclusions. The study adopts Georg Lukács’s Socialist Realism theory as its theoretical framework, examining the ways in which the short story reflects social reality from Lukács’s perspective. The findings indicate several major social issues, including socioeconomic inequality, social hypocrisy in the moral judgment of women, gender inequality within a patriarchal structure, slander, and the tragic consequences of delayed truth recognition.